Formulation and Characterization of Uncaria gambir (U. gambir) Extract Cream as an Anti-Psoriasis Candidate: In Silico and In Vitro Studies - Abidin, Khoirul Rista; Nurhidayattulloh, Ariffialdi; Siregar, Febrina; Dermawan, Abdurrafi Maududi; Dwisari, Fath; Oktaviria, Oktaviria; Suchi, Suchi; Indriani, Melly; Putri, Firda Aulia; Prasetyaningsi, Hernyati; Shofia, Shofia (Indonesian Journal of Chemical Research, 2026)
Background: Psoriasis is a chronic inflammatory skin disorder in which oxidative stress and COX-2–mediated pathways contribute to disease progression. Conventional topical therapies, particularly corticosteroids, are effective but associated with adverse effects and limited mechanistic targeting. Objective: This study investigated Uncaria gambir (U. gambir) extract as a natural anti-psoriasis candidate in a topical cream formulation through phytochemical, antioxidant, in silico, and physicochemical evaluations. Methods: The extract was screened for phenolic and flavonoid content and evaluated for DPPH radical scavenging activity (IC₅₀). Molecular docking of catechin against the COX-2 receptor was performed using quercetin as a reference. Cream formulations containing varying extract concentrations were assessed for pH, spreadability, and adhesiveness. Results: U. gambir extract exhibited very strong antioxidant activity (IC₅₀ = 6.84 ppm), falling within the range of highly active antioxidants, although less potent than vitamin C. Catechin showed stable COX-2 binding (−4.76 kcal/mol). The 4.5% cream formulation (F2) demonstrated optimal properties, with a skin-compatible pH (~7.5) and good spreadability (~5.5 cm). Conclusion: U. gambir extract shows promising potential as a natural topical agent targeting oxidative stress and inflammation in psoriasis, supporting further in vivo and clinical validation.